2012
DOI: 10.1115/1.4006980
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Thermal Elastic Deformation Analysis on the Piston/Cylinder Interface of Axial Piston Machines

Abstract: The piston/cylinder interface of swash plate–type axial piston machines represents one of the most critical design elements for this type of pump and motor. Oscillating pressures and inertia forces acting on the piston lead to its micro-motion, which generates an oscillating fluid film with a dynamically changing pressure distribution. Operating under oscillating high load conditions, the fluid film between the piston and cylinder has simultaneously to bear the external load and to seal the high pressure regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…Therefore, the thermal deformation was increasingly introduced to relevant studies of the lubrication performance of the piston skirt. Pelosi and Ivantysynova [26] built a fully coupled simulation model for the piston/cylinder interface of axial piston machines and validated the model by comparing the prediction values with measurements of the fluid film boundary temperature distribution. The influence of the heat transfer and solids-induced thermal elastic deformation on the piston skirt-cylinder lubricating interface behavior was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the thermal deformation was increasingly introduced to relevant studies of the lubrication performance of the piston skirt. Pelosi and Ivantysynova [26] built a fully coupled simulation model for the piston/cylinder interface of axial piston machines and validated the model by comparing the prediction values with measurements of the fluid film boundary temperature distribution. The influence of the heat transfer and solids-induced thermal elastic deformation on the piston skirt-cylinder lubricating interface behavior was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure measurements aimed at validating an FSI-Thermal model of the piston cylinder interface in axial piston machines have been presented in [21,12,22]. More recently, temperature measurements have been used to validate the simulation results of an FSI-thermal model of the cylinder block-valve plate interface in swash plate type axial piston machines [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the above studies made the assumption of an isothermal fluid film and solid components, in addition to neglecting the deformation of the solids due to thermal loads. Detailed models of lubricating gaps other positive displacement machines, such as axial piston machines, have shown in the past that in addition to accounting for deformation of the solids due to pressure it is also important to account for thermal effects in lubricating gaps [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works of the author's research group have demonstrated that the fluid film behavior can be predicted with good level of accuracy only when multiphysics simulation model are introduced [1], [5], [6] for the piston / cylinder interface, [7], [8] for the slipper / swash plate interface and [9], [10], [2] for the cylinder block / valve plate interface. The three interfaces are subject to the same physical phenomena and therefore can be modeled using the same basic structure.…”
Section: Prediction Of Power Losses In the Lubricating Interfaces Of mentioning
confidence: 99%